Exploring the relationship between behavior matching and interlocutor perceptions in L2 interaction. (October 2022) - McDonough, Kim; Kim, Yoo Lae; Uludag, Pakize; Liu, Chen; Trofimovich, Pavel
Abstract: Alignment in nonverbal behavior can be understood through reference to behavior matching, which is the tendency to adopt the behaviors, postures, or mannerisms of a conversational partner. Although behavior matching is believed to occur unintentionally and unconsciously, its occurrence is associated with how interlocutors perceive each other. Drawing on corpus data of conversations between English second language (L2) speakers, this study examines the relationship between behavior matching and interlocutor perceptions, which were measured through post-task ratings of partner collaboration and motivation. Conversations ( N = 51) between 102 English L2 university students were coded for nonverbal behaviors in five categories (face, head, hand, posture, self-adaption), and each behavior was coded as being matched or not matched by the interlocutor. The proportion of matched behaviors per dyad in each category were correlated with the mean motivation and collaboration partner ratings, and a linear regression model identified hand behavior matching as a significant predictor of partner motivation. Potential implications and avenues for future research about nonverbal alignment are discussed. Highlights: Behavior matching is the tendency to adopt the behaviors, postures, or mannerisms of a conversational partner. English L2 speakers' conversations were analyzed to identify behavior matching. They rated their partner's motivation and collaboration immediately after the conversation. Hand movement behavior matching positively predicted motivation ratings.